2020
DOI: 10.1007/s13205-020-02539-0
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective property of Trifolium repens leaf extract against paracetamol-induced kidney damage in mice

Abstract: Paracetamol-induced toxicity is one of the major drawbacks in the treatment of inflammatory conditions. The present study was performed to find out the impacts of phenolic compounds in the Trifolium repens (white clover) leaves (TR) against the paracetamol-induced nephrotoxicity in mice. The extract was administered orally to mice in different doses (1, 2, and 3 mL having a dry mass of 11.0 mg/mL) along with paracetamol (300 mg/kg) alone or in combination. Kidney histology, serum renal function tests, serum el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In another study, Ahmad and Zeb found that male mice given silymarin 100 mg/kg BW/day after receiving paracetamol 300 mg/kg BW/day for two weeks showed no significant differences in serum albumin, total serum protein, or blood biochemical like serum urea and serum creatinine compared to untreated control animals. Also, it has positive benefits with increased levels of GSH in renal tissues and a considerable drop in TBARS levels compared to mice treated with paracetamol (63).…”
Section: Reports On Silymarin's Nephroprotective Impact In Paracetamo...mentioning
confidence: 99%
“…In another study, Ahmad and Zeb found that male mice given silymarin 100 mg/kg BW/day after receiving paracetamol 300 mg/kg BW/day for two weeks showed no significant differences in serum albumin, total serum protein, or blood biochemical like serum urea and serum creatinine compared to untreated control animals. Also, it has positive benefits with increased levels of GSH in renal tissues and a considerable drop in TBARS levels compared to mice treated with paracetamol (63).…”
Section: Reports On Silymarin's Nephroprotective Impact In Paracetamo...mentioning
confidence: 99%
“…Elevated APAP doses decrease the concentration of glutathione, causing NAPQI to react with cellular proteins in the liver and kidneys, leading to cellular destruction. Consequently, an increased level of NAPQI may serve as an intermediary for oxidative damage, intensifying hepatocellular and nephrocyte necrosis (Ahmad and Zeb 2020). Despite renal toxicity being less prevalent than hepatic toxicity in cases of APAP overdose, damage to renal tubules and acute renal failure can occur, potentially leading to fatality in both humans and animals (Chinnappan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the utilization of conventional therapeutic drugs to treat or prevent renal toxicity caused by APAP remains limited and is associated with various side effects. As a result, profound scientific efforts are currently confronted with challenges in the exploration of alternative therapeutic agents or supplementary agents for treatment or prevention (Ahmad and Zeb 2020). Herbal medicine's healing properties stem from its intricate chemical composition (Gaikwad et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overdose of paracetamol causes renal failure in humans [ 6 ]. Paracetamol severely affects kidneys by reducing kidney weight, biochemistry of renal profile, serum electrolytes and glutathione in mice [ 7 ]. At therapeutic doses, paracetamol is safe but overdosage causes renal toxicities and renal failure in rats and animal models [ 8 ].…”
Section: Introductionmentioning
confidence: 99%